Opinion 2358: Balintus d’Abrera, 2001, Gulliveria d’Abrera & Bálint, 2001, Salazaria d’Abrera & Bálint, 2001, Megathecla Robbins, 2002 and Gullicaena Bálint, 2002 (Insecta, Lepidoptera, Lycaenidae): priority maintained - ICZN (Bulletin of Zoological Nomenclature, 2015)
The Commission has not approved the request to rule under its plenary power on the status of several generic names in the Lycaenidae. Instead, under Articles 78.2.3 and 81.2.4 of the Code, the Commission, using its specific powers, confirms the availability of all the new generic names proposed in d’Abrera (2001) and consequently the availability of any replacement names proposed for any of them.
Keywords: Nomenclature; taxonomy; LYCAENIDAE; Annamaria; Balintus; Chopinia; Eucharia; Gullicaena; Gulliveria; Lamasina; Lucilda; Megathecla; Pedusa; Riojana; Salazaria; hairstreak butterflies; Neotropics